THE CHANGES OF GEORGIA’S SECURITY POLITICS AFTER 2012 AND THE SHIFTING SECURITY IDENTITY - Janeliūnas, Tomas (Politologija, 2017)
After the Russian – Georgian war in 2008 the conflicts over separatist regions of Abkhazia and South Ossetia became typical frozen conflicts. At the same time, Georgia’s aspiration to get the NATO membership also has become frozen. The treat of Russia has been securitized by the government of President Michael Saakashvili and has been clearly reflected in all main strategic documents of Georgia. The NATO membership was the main goal of Georgia’s security and foreign policy even before 2008. According to many authors, this strategic choice of allying against potential aggressor is a logical option for a small state seeking security. Right after the 2008 war the support for the NATO membership among Georgian society was extremely high – 70 percent was “fully supporting” the NATO membership and another 17 percent “somewhat supporting”. However, the mood of Georgian population has started to shift quite soon and the trust for Saakashvili has diminished. The society has become tired over the securitization of Russia without clear perspective of the NATO membership. The perspective of the NATO membership in the eyes of Georgian population has not been abolished but rather postponed: the support for the membership during 2010–2012 was still high despite softer attitude towards Russia. After the change of government in 2012–2013 Georgia in fact suspended the development of national security sector. Georgian politicians since 2012 have softened the rhetoric towards Russia and have chosen a tactics of “let wait and do not provoke”. The attempts to desecuritise Russia in Georgia is in opposite to the increased securitisation of Russia in NATO and the EU. The potential threats coming from Russia have been deliberately desecuritized in Georgia in seeking to avoid any increasing tension with Russia and to evade the potential aggressive reaction from Moscow. The article relays on the constructivist approach and argues that the changes in Georgia’s security and foreign policy did occur due to the dynamics of security identity. The dynamics of social identity in Georgia might have happened because of the changes in its domestic politics – a tacit agreement between Georgia’s society and political elite to review the priorities and values of national politics – as well as the changes in the international environment that restricted certain choices of security strategies for Georgia. Having in mind the security strategies prescribed for small states in academic literature, most often Georgia remains in an undefined and uncertain phase which could be labelled as “strategic waiting”. Georgia is still aspiring for the Euro-Atlantic integration and seeking to not confront Russia at the same time. However, the article concludes that such an interim status in between “alliance” and “sitting of the fence” (or preserving an autonomy) is lacking clear argumentation and remains very dependent on external influences, first of all – on the dynamics of relations between the West and Russia.